A BIM-based Construction Supply Chain Framework for Monitoring Progress and Coordination of Site Activities. (2016) - Getuli, Vito; Ventura, Silvia Mastrolembo; Capone, Pietro; Ciribini, Angelo L.C.
Abstract: In spite of the growing implementation of Computer-aided technologies and Building Information Modeling (BIM) in AEC industry, building activities in construction sites are ineffectively monitored even now. Current formats of reporting and communicating the construction progress (e.g., textual progress reports, progress lines, and photographs) may not properly and quickly communicate the construction progress. In the proposed research the capability to communicate progress information right away and to share an Interactive Building Model (IBModel) are identified as the key components for successful management of the site and the supply chain network. This is carried out establishing the involved actors (Owner, Site Director, Site Safety Coordinator, Construction Companies and Suppliers) and setting them several options for the information management and visualization within the BIM environment. The monitoring system comes from the integration of the building and construction site model bestowing the visualization of site conditions on a set of graphical parametric rules, such as: chromatic visualization of building components referred to objects' completion percentage; thematic views, automatically extracted and updated, representing the real site conditions; and so forth. The monitoring system, supported by the BIM-based visualization model and managed in a Cloud computing seems to be one of the right directions for improving safety condition on one hand and site productivity and control on the other one.